The young pope [videorecording (DVD)] - Law, Jude, 1972-; Keaton, Diane; Orlando, Silvio, 1957-; Cámara, Javier (HBO Home Entertainment, 2017)
The fictional story of a newly elected pope, the youngest in history and first-ever American, whose audacity, independence, and arch-conservatism wreak havoc within the Vatican.